PENDAMPINGAN PENGEMBANGAN KINERJA GURU DI MASA PANDEMI COVID-19 - Rasmulia Sembiring; Robinhot Gultom; Sahat P. Remus Silalahi; Siti Normi; Winarto Winarto; Saur Meliana; Sondang Ni Bulan Marbun; Romel Sitohang; Rio Junjung Tambunan; Maludin Panjaitan; Jon Henri Purba (Jurnal Pengabdian Pada Masyarakat METHABDI, 2021)
The purpose of community service at HKBP Padang Bulan Elementary and Junior School is to provide input for teachers, principals, regarding efforts to improve teacher performance. Thus, teachers are expected to improve the quality of education. The efforts that can be taken are the establishment of institutions that foster the performance of teachers and education staff, supervision of school principals, teacher consultation activities, bringing in motivators, providing adequate facilities, and providing adequate welfare. Teachers are expected to develop themselves and always follow the changes that occur.